Effect of Training Exercise on Urinary Brain-derived Neurotrophic Factor Levels and Cognitive Performances in Overweight and Obese Subjects: A Pilot Study. Issue 1 (February 2017) - Russo, Angelo; Buratta, Livia; Pippi, Roberto; Aiello, Cristina; Ranucci, Claudia; Reginato, Elisa; Santangelo, Valerio; DeFeo, Pierpaolo; Mazzeschi, Claudia
Exercise-mediated, brain-derived neurotrophic factor induction benefits health and cognitive functions. The multifaceted interplay between physical activity, urinary brain-derived neurotrophic factor levels and cognitive functioning has been largely neglected in previous literature. In this pilot study, two bouts of training exercise (65% and 70% of heart rate reserve) influenced urinary brain-derived neurotrophic factor levels and cognitive performances in 12 overweight and obese participants. Percent heart rate reserve, expenditure energy, brain-derived neurotrophic factor urinary levels and cognitive performances were measured before and after the exercise. No significant variations in energy expenditure were observed, while differences of heart rate reserve between two groups were maintained. Both bouts of training exercise induced a similar reduction in urinary brain-derived neurotrophic factor levels. Only visuo-spatial working memory capacity at 65% of heart rate reserve showed a significant increase. These findings indicate a consistent effect of training exercise on urinary brain-derived neurotrophic factor levels and cognitive factors in overweight and obese participants.